Діалектика необхідності й свободи у трудових правовідносинах - Занфірова, Т.А. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
В статье рассматриваются проблемы соотношения необходимости и свободы в правосознании субъектов трудовых отношшений. Главное внимание сосредоточено на философском анализе указанных категорий. In the article the problems of correlation of necessity and freedom are examined in the legal awareness of the subjects of labour relations. Central attention is concentrated on the philosophical analysis of the indicated categories.